Sliding mode control power system stabilizer for a single machine infinite bus system - Safie, Sairul Izwan (Penerbit UTM, 2007)
Stability is a condition of equilibrium between opposing forces. The mechanism by which interconnected synchronous machines maintain synchronism with one another is through restoring forces. Under steady state condition, there is equilibrium between the input mechanical torque and the output electrical of each machine.